The holy drama : Persian passion play in modern Iran - Mahani, Mahnia A. Nematollahi (Silsilat al-dirÄsÄt al-ÄªrÄnÄ«yah., 2013)
Persian passion play or ta'ziya depicts the role of the Prophet's granddaughter Zeynab during the tragic death of the third Shiite Imam Hoseyn in Karbala in 680. This book depicts how Zeynab has become a role model in modern Iranian society, especially during the Islamic Revolution and the Iran-Iraq War.